ChemInform Abstract: Cascade Arylalkylation of Activated Alkenes: Synthesis of Chloro‐ and Cyano‐Containing Oxindoles. Issue 29 (July 2015) - Li, Xueqin; Xu, Jian; Gao, Yuzhen; Fang, Hua; Tang, Guo; Zhao, Yufen
Abstract The oxidative cyclization is carried out in dichloromethane or acetonitrile to produce the desired oxindole structures bearing a functionalized side chain at position 3.